(untitled) (Experimental biology, 2016)
Development of scientific and technological bases of genetic resources conservation of endemic Allochrusa gypsophiloides (Regel) Schischk (Turkestan soaproot - TSR) - valuable domestic source of technical and medical saponin to produce economically important product is an actual problem. Allochrusa gypsophiloides belongs to the family Caryophyllaceae Juss. officially includes into the national pharmacopoeia, and had practical applications in many fields of the domestic industry. For many years TSR was exported as a valuable source of plant saponin and industrial soap roots harvesting was carried out on the territory of the republics of Central Asia and the Kazakh SSR. In the result of many years of intensive and unsystematic blanks TSR was recorded in 1981 in the Red Book of the Kazakh SSR as a rare species with a strongly decreasing population. The aim of this study was a qualitative and quantitative study of saponins from Allochrusa gypsophiloides collected in South Kazakhstan region of the Republic of Kazakhstan. The results of qualitative reactions show the presence of triterpenic saponins in plant material. The aglycone of triterpenic saponins as oleanolic acid was identified by thin layer chromatography in variety solvent systems after acid hydrolysis. The content of triterpenic saponins in Allochrusa gypsophiloides collected during flowering–fruiting phase was determined by the spectrophotometric method. The content of the sum of triterpenic saponins in terms of oleanolic acid in roots was 7,63% and 2,29% in aerial part of plant. The foaming and hemolytic activities of saponins extracted from Allochrusa gypsophiloides were evaluated. High surface (foaming ratio 1:6660) and significant hemolytic activities HI 3333 for aqueous and ethanolic extracts from roots differing with a high saponins content compared to aerial part of Allochrusa gypsophiloides it was revealed. The obtained data allows to assert that the creation of the raw materials base of Allochrusa gypsophiloides in the South Kazakhstan region is appropriate and to recommend Allochrusa gypsophiloides for further introduction as an irreplaceable source of triterpene saponins with high biological activity.